JUAL-BELI CENGKEH BORONGAN DI KARANG MULYO SUDIMORO PACITAN PERSPEKTIF FIKIH MU’AMALAH - Kadenun Kadenun Kadenun; Miftakhul Jannah (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2022)
Along with developing the community paradigm, the methods in sharia business transactions have also experienced significant developments. For example, in Karang Mulyo Village, Sudimoro Pacitan, in the past, buying and selling cloves only happened to goods that were ready to be sold, so there was money there. But now traders have the initiative to buy cloves in bulk. In the implementation of buying and selling cloves on a wholesale basis in Karang Mulyo Sudimoro Village, Pacitan, because people need money faster and want an easier clove sales process. The implementation of the sale and purchase is by selling the cloves still on trees that are ready to harvest, but it is not clear from the weight of the cloves. The implementation of buying and selling wholesale is still not fully carried out by the community because cloves are part of the permanent income of the community in Karang Mulyo Village, so if they are sold in bulk, they must be rethought. So it is important for the author to study more deeply the implementation of buying and selling cloves in bulk so that it is clearer. The objectives of this research are: (1) To find out the mechanism of wholesale clove buying and selling transactions in Karang Mulyo Sudimoro Pacitan (2) To find out the perspective of muamalah fiqh on price determination and profit buying and selling of wholesale cloves in Karang Mulyo Sudimoro Pacitan? While the method used in this study is to use a qualitative descriptive method and for data collection techniques, namely through observation, interviews, and documentation. The location of this research is in Karang Mulyo Village, Sudimoro District, Pacitan Regency. Based on data analysis, it can be concluded that: (1) The transaction mechanism used in the wholesale sale and purchase of cloves is through mutual agreement, and there is an element of mutual pleasure between them. (2) The determination of the price in buying and selling cloves in bulk is in accordance with mu'amalah fiqh because its implementation uses the estimation method; while the profits obtained by farmers and contractors cannot be determined, the profit-taking is still reasonable.